Dear Photograph: Online Pictures and Traces of the Past (Cinéma & Cie. Film and Media Studies Journal, 2013)
By analyzing the photographic archive of Dear Photograph (dearphotograph.com) - a website that intends to use pictures of the past as traces of personal memories - this article will focus on the relationship between memory and photography in the digital age, and on the value attributed to the sharing of private snapshots on the Web. I will analyze the images chosen by the participants to portray their own past, underlining both old and new uses of photographs, and pictures will be read together with their captions, as a unique "imagetext". Even if images seem to play a crucial role in memory's representation, their relationship with their verbal explanations reveals some crucial aspects of the sharing of private photographs on the Web. Captions make family pictures "readable" also for an extraneous observer and distinguish similar photographs one from another: while enlarging the intimate context that characterizes the reading of family pictures, the Web amplifies the properties of analogue photography, which ratifies the belonging of an individual to a group and transforms personal recollections into a shared (and sharable) memory.